Analisis Akuntabilitas Kinerja Sekolah dari Perspektif Teori Pemangku Kepentingan - Ade Palupi; Queentina Adhella Prudencia; Ade Wirman Syafei; Jumansyah Jumansyah (Jurnal Eksplorasi Akuntansi, 2024)
This research explains on how a school accounts for its performance due to to comply its accountability to its stakeholders. Meanwhile, the purpose of this study is to enrich stakeholder theory discourse on the application of performance measurement in schools. This is a case study research by using qualitative approach. A private high school in the East Jakarta to be a case. Data is collected through documentation and interviews with the principal, two vice principals and an officer of school public relations. This study finds (1) the stakeholders of private school consist of the government, the school foundation, and parents. (2) The school conducts performance measurement as a tool for complying school’s accountability. (3) School prepares some reports in term of learning resources, financial resources, and asset management to report school’s performance for its stakeholders. (4) As school managing the three types of resources, it creates value, namely the excellent level of students’ academic and non-academic quality. This paper concludes that using performance measurement and report it to its stakeholder for complying accountability is a form of school’s interaction with stakeholders. This relationship is significant for school to attain its value in delivering education service.